Carbon Nanotubes for Interconnects Process, Design and Applications - Todri-Sanial, Aida; Dijon, Jean; Maffucci, Antonio (Springer International Publishing : Imprint: Springer, 2017)
This book provides a single-source reference on the use of carbon nanotubes (CNTs) as interconnect material for horizontal, on-chip and 3D interconnects. The authors demonstrate the uses of bundles of CNTs, as innovative conducting material to fabricate interconnect through-silicon vias (TSVs), in order to improve the performance, reliability and integration of 3D integrated circuits (ICs). This book will be first to provide a coherent overview of exploiting carbon nanotubes for 3D interconnects covering aspects from processing, modeling, simulation, characterization and applications. Coverage also includes a thorough presentation of the application of CNTs as horizontal on-chip interconnects which can potentially revolutionize the nanoelectronics industry. This book is a must-read for anyone interested in the state-of-the-art on exploiting carbon nanotubes for interconnects for both 2D and 3D integrated circuits. Provides a single-source reference on carbon nanotubes for interconnect applications; Includes complete coverage of current Cu-based interconnect problems for both 2D and 3D interconnects; Covers topics from modeling, simulation, analysis, design and characterization, in order to provide a broad view of the application of carbon nanotubes for interconnects.